Foreløbig Oversigt over Landbrugets Driftsresultat i Regnskabsaaret 1938—39. - Nielsen, Axel (Tidsskrift for Landøkonomi, 2018)
Foreløbig Oversigt over Landbrugets Driftsresultat i Regnskabsaaret 1938—39.